The application of distributed optical strain sensing to measure the strain distribution of ground support members - Bradley Forbes; Nicholas Vlachopoulos; Andrew J. Hyett (Canadian Science Publishing, 2018)
A distributed optical strain-sensing technique is presented as a solution for measuring the strain distribution along ground support members used in tunnelling and mining works. The technique employs a Rayleigh optical frequency domain reflectometry technology, which measures strain at a spatial resolution of 0.65 mm along the length of a standard optical fiber. A rationale for selecting this technology as a potential monitoring technique for ground support elements over alternative commercially available technologies is discussed. The development of a technique to couple optical fiber sensors with rock bolt, umbrella arch, and cable bolt support members is also demonstrated. A robust laboratory investigation of such optically instrumented support members demonstrated the capability of the technique to capture the expected in situ support behaviour in the form of coaxial, lateral, and shear loading arrangements as would be anticipated in the field. Moreover, the micro-scale data obtained by this optical sensing technique are shown to provide unprecedented insight into the local/micro-scale geomechanistic complexities associated with the bearing capacity of ground support members, especially when compared with data obtained by discrete strain-sensing technologies.